2016
DOI: 10.1099/jmm.0.000274
|View full text |Cite
|
Sign up to set email alerts
|

Enterohepatic Helicobacter spp. in cats with non-haematopoietic intestinal carcinoma: a survey of 55 cases

Abstract: Several enterohepatic Helicobacter spp. (EHS) have been isolated from cats. Despite the reported association between EHS infection and intestinal neoplasia in other species, this association has not been explored in cats. In this study, 55 non-haematopoietic feline intestinal carcinoma cases were histopathologically evaluated. In contrast with prior reports, large intestinal (LI) carcinoma was observed with greater frequency (61 %) relative to small intestinal (SI) carcinoma (35 %). There was a significant ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
3
7
2
Order By: Relevance
“…46 In a recent study, FISH showed that the presence of enterohepatic helicobacter was significantly associated with poorly differentiated large intestinal adenocarcinoma in cats. 48 Our results showed no significant difference in Helicobacter spp. bacterial counts in GI biopsies of cats with small cell GI LSA compared to GI biopsies of cats with IBD.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…46 In a recent study, FISH showed that the presence of enterohepatic helicobacter was significantly associated with poorly differentiated large intestinal adenocarcinoma in cats. 48 Our results showed no significant difference in Helicobacter spp. bacterial counts in GI biopsies of cats with small cell GI LSA compared to GI biopsies of cats with IBD.…”
Section: Discussioncontrasting
confidence: 48%
“…induces host responses influencing risk of oncogenesis, and promotes chronic gut inflammation in humans and mice 46. In a recent study, FISH showed that the presence of enterohepatic helicobacter was significantly associated with poorly differentiated large intestinal adenocarcinoma in cats 48. Our results showed no significant difference in Helicobacter spp.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…To date, more than 37 Helicobacter species have been identified in addition to H. pylori (Péré-Védrenne et al, 2017 ). Furthermore, non- H. pylori Helicobacters (NHPH) have been shown to infect both humans and animals, and NHPH infections are associated with intestinal carcinoma, and mucinous adenocarcinoma (Swennes et al, 2016 ). Despite the demonstrated association between NHPH and disease, most studies to date have investigated H. pylori in humans; thus, it is necessary to characterize NHPH and elucidate its role in the GI tract of wild rodents which are potential Helicobacter carriers (Taylor et al, 2007 ; Mladenova-Hristova et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…in cats with nonhematopoietic intestinal carcinoma (55 cases) was shown to be as high as 56%, and one or more speciesspecific assays were positive for Helicobacter bilis, Helicobacter canis, or Helicobacter marmotae. The presence of NHPH was significantly associated with large intestinal carcinoma (68%) and mucinous adenocarcinoma (92%) 11. Sabry et al evaluated 149 animals and 10 human fecal samples for the presence of Helicobacter sp.…”
mentioning
confidence: 99%